PENGARUH MOTIVASI DAN PERSEPSI TENTANG PEMBELAJARAN MATA DIKLAT KOMPETENSI KEJURUAN APK TERHADAP HASIL BELAJAR SISWA DI SMK NEGERI 1 PAMEKASAN - Wulandari, Ruri Nurul Aeni (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2015)
The purpose of this research was to analyze the influence of motivation and perceptions about vocational competency lessons on student learning results in SMKN 1 Pamekasan. The population consists of 119 students of class XI SMKN 1 Pamekasan academic year 2013-2014. 92 students as sample are taken by simple random sampling. Technique of data collection using questionnaires and documentation. This research used the quantitative approach and data were be analyzed using multiple linear regression. The results show that the partially and simultaneously motivation and perceptions have a significant effect on student learning results in SMKN 1 Pamekasan. greatest Influence is perceptions on student learning by 37%